Eksistensi Jurnalisme Surat Kabar pada Era Media Digital di Indonesia - Aguswandi; Rahmawati Haruna (Program Studi Ilmu Komunikasi, FISIP Unismuh Makassar, 2026)
This research explores the adaptation of the newspaper industry in Indonesia to shifts in the media business triggered by advancements in digital technology. Over the last two decades, there has been a significant shift in how the public accesses information, creating a stark contrast between online media consumers and print newspaper readers. This phenomenon poses a major challenge for conventional newspapers to transform in order to remain relevant. Using a literature review method, this study analyzes various relevant sources to identify factors influencing the sustainability of newspaper journalism in the digital era. The results of the study indicate that there are three formulations of the integration model of the existence of newspaper journalism, namely the structural-economic dimension, the professional-cultural dimension of journalism, and the theoretical dimension: Integration of convergence-mediamorphosis-political economy. The conclusion of this study confirms the theoretical contribution that the success of newspaper journalism in Indonesia is highly dependent on the ability of media convergence and mediamorphosis to change the consumption behavior of an increasingly digital society. By utilizing existing opportunities, newspapers can continue to contribute in providing quality and reliable information to the public, even though they have to compete fiercely with digital media.